Integration of Da'wah Communication and Disaster Mitigation Through Disaster Monitoring - Nadhirothul Afirda; Naufal Rifqi Nasution (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The high intensity of natural disasters in Pacet District positions the area as a priority for efforts in disaster safety and preparedness. This study aims to understand the strategies for delivering dakwah (Islamic preaching) messages that address the needs to foster a disaster-resilient and effective community through the Ngaji Bencana program. Using a hermeneutic phenomenological approach, the findings reveal that PC LPBI NU Mojokerto has successfully implemented disaster mitigation efforts by integrating local traditions, reactivating traditional knowledge, involving religious leaders, and utilizing social media in ways that align with Islamic preaching values. The study indicates that approaches rooted in local wisdom and religious involvement play a crucial role in raising community awareness. It recommends the necessity of long-term, multi-stakeholder engagement to uphold the sustainability and effevtivenness of the Ngaji Bencana initiative.